Chlorine activation and chemical ozone loss deduced from HALOE and balloon measurements in the Arctic during the Winter of 1999-2000 - Müller, R.; Tilmes, S.; Arvelius, J.; Russell III, J. M.; Grooß, J. U.; McKenna, D. S.; Müller, M.; Schmidt, U.; Toon, G. C.; Stachnik, S. S.; Margitan, J. J.; Elkins, J. W. (Journal of Geophysical Research: Atmospheres, 2003)
[1] We employ Halogen Occultation Experiment (HALOE) observations and balloon-borne measurements (on the large Observations of the Middle Stratosphere [OMS] and Triple balloons, as well as on two small balloons) to investigate ozone loss in the stratospheric vortex in the 1999-2000 Arctic winter. Using HF and CH4 as long-lived tracers, we identify chlorine activation and chemical ozone destruction in the polar vortex. Reference relations, representative of chemically undisturbed "early vortex'' conditions, are derived from the OMS remote and in situ balloon measurements on 19 November and 3 December 1999, respectively. Deviations from this "early vortex'' reference are interpreted as chemical ozone loss and heterogeneous chlorine activation. The observations show an extensive activation of chlorine; in late February 2000, the activation extends to altitudes of 600 K. Between 360 and 450 K chlorine was almost completely activated. At that time, about 70% of the HCl column between 380 and 550 K was converted to active chlorine. Furthermore, the measurements indicate severe chemical ozone loss, with a maximum loss of over 60% in the lower stratosphere (415-465 K) by mid-March 2000. Substantial ozone loss was still observable in vortex remnants in late April 2000 (80 +/- 10 Dobson units [DU] between 380 and 550 K). The average loss in column ozone between 380 and 550 K, inside the vortex core, in mid-March amounted to 84 +/- 13 DU.